Closing the Capability Gap in Tackling Precarious Work - Teng-Calleja, Mendiola (Archīum Ateneo, 2023)
Precarious workers often receive relatively lower wages than those in formal employment. Determining the difference between wages that promote a decent life and the current income received by workers can orient ways of tackling precarious work conditions. In this chapter, we present both the process and results from a study conducted in the Philippines on one of the first weighted psychometric approaches that can be utilized in enriching our understanding of fair income in the context of precarity. Our aims are two-fold. First, we propose a psycho-economic gauge of precarity, which links individual assessments of what constitutes a decent life and the wage level that may enable the attainment of such life. We argue that this alternative approach is important in refocusing the attention to a more worker-centric perspective on the issue of precarity. Second, we make a case for the feasibility of how Human Resource Management practitioners and employers or organizations can greatly contribute to minimizing precarity by ensuring provision of decent work through living wages. We consequently gave suggestions on how organizations can provide fair income to workers through a myriad of strategies that can be considered based on what may work in specific contexts.